2019
DOI: 10.1177/1460458219833112
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of introducing inpatient electronic prescribing on prescribing errors? A naturalistic stepped wedge study in an English teaching hospital

Abstract: Most studies evaluating the impact of electronic prescribing on prescribing safety have used comparatively weak study designs such as uncontrolled before-and-after studies. This study aimed to apply a more robust naturalistic stepped wedge study design to compare the prevalence and types of prescribing errors for electronic prescribing and paper prescribing. Data were collected weekly during a phased electronic prescribing implementation across 20 wards in a large English hospital. We identified 511 (7.8%) err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Whilst evidence shows a variation amongst prescribing systems in reducing errors, our results add to research that indicates there are fewer incomplete prescriptions with electronic prescribing systems [27]. This was specifically true where mandatory fields were required prior to a prescription being accepted by the system.…”
Section: Key Findingssupporting
confidence: 49%
See 1 more Smart Citation
“…Whilst evidence shows a variation amongst prescribing systems in reducing errors, our results add to research that indicates there are fewer incomplete prescriptions with electronic prescribing systems [27]. This was specifically true where mandatory fields were required prior to a prescription being accepted by the system.…”
Section: Key Findingssupporting
confidence: 49%
“…Electronic prescribing systems are considered an important strategy in reducing medication errors including those involving insulin [10,24,25]. It is important to note however, that there is conflicting evidence within the literature internationally on the impact of electronic prescribing in reducing inpatient medication errors [26][27][28]. In 2019, a report from the Healthcare Safety Investigation Branch (HSIB) summarised that although the implementation of electronic prescribing is associated with a greater than 50% reduction in medication errors, different types of electronic prescribing and medicines administration (ePMA) systems are available, and this can lead to variation in how medicines are prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…The prescribing error rate of 3.3% found in this study falls in the range of other such studies done on in-patients wherein the error rate has been reported from 1.5% to 15%. 8,[14][15][16] The reported prescribing error rates in studies done on out-patients have been much higher i.e. 65% or greater.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Dean Franklin and Puaar 20 describes the result of a stepped wedge study of the impact of introducing electronic prescribing on prescribing errors in one hospital with 20 wards. The study nicely demonstrates the importance of having a robust study design that allows a nuanced analysis of the effect of technology on process and outcome measures.…”
Section: The Contribution Of the Papers In This Special Issuementioning
confidence: 99%